Land Productivity and Land Equivalent Ratio of Agroforestry System in Marena Customary Forest, Enrekang Regency, South Sulawesi Province, Indonesia - Samrin, Samsul; Millang, Syamsuddin; Ridwan; Daud, M (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Applying agroforestry system in the customary forest area plays a significant role in increasing the productivity of the community’s land because it will increase the economic value and welfare of the customary community. This study aims to analyze the agroforestry system’s land productivity and land equivalent ratio in the Marena Customary Forest (MCF) area, Enrekang Regency. This research used a survey method involving observation, questionnaires, and interviews with sample respondents who owned land and applied agroforestry systems in the MCF. Data obtained from interviews and field observations were then analyzed descriptively. The study revealed that applying agroforestry systems in the community-managed MCF can increase land productivity, showing the value of land productivity of IDR 20,512,208/ha/year. The agroforestry system’s land equivalent ratio (LER) amounted to 2.34. This shows that applying the agroforestry system is considered capable of increasing land productivity and the income and welfare of the indigenous people of Marena. Keywords: agroforestry, customary forest, land equivalent ratio, land productivity